RE-INTEGRASI EPISTIMOLOGI AGAMA DAN SAINS. - Muharir Alwan (Jurnal Al-Muta`aliyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2016)
The integration discussion of scientific knowledge in religion dichotomy stream  and science are certainly to develop for establish anti teas to the secular of western science development, the art penetration that supported by empiric rationality as a truth measure that developed by western country were give the influence to the science development in this era. The science that developed and sourced from western country was escaped from the theological, the rationality reinforcing  as a truth measure was grated the framework idea and no except for Islamic community. The religion and science dichotomy was ignored the religion function to the knowledge, so it was make the science must be stand on it self without intervention of theology, for the more effect, will be happened the treating as a God (pendewaan) to the rationality, a reduction in value of godly to reconstruct the science, dry value of spirituality in human pragmatic-opportunist attitude. When the science are introduced to the Islamic world through the west imperialism, it makes a hard dichotomy between religion and science, after explaining to the validity and scientific status between one each other the dichotomy more and more to become acute. Fundamentalist group are assume that study about science is Bid’ah ( Bid’ah is something that prophet Muhammad saw. never do it), even though the supporter of science  are assume the knowledge of religion as a scientific-pseudo or just a mythology, because it’s not speak about empiric-fact. The corroborate Co-optation of western culture to the science development must be balanced with the reinforcing of scientific knowledge that be based on the holy Qur’an as an epistemology basic in reconstruct the religion and science integration, so the science be a support of truthfulness of revelation.